Evaluation of the Implementation of the Youth Care Health Service Program in the West Lingkar Health Center of Bengkulu City - Oktarianita, Oktarianita; Pratiwi, Bintang Agustina; Febriawati, Henni; Yanuarti, Riska (Disease Prevention and Public Health Journal, 2021)
Background: One of the strategies to overcome adolescent problems is the formation of the Youth Care Health Service Program or Pelayanan Kesehatan Peduli Remaja (PKPR). PKPR itself is a health service program aimed at adolescents and is a forum for overcoming adolescent problems. This study aimed to analyze the implementation of the PKPR program in the working area of the West Lingkar Health Center. Method:Â  This research was a qualitative descriptive study conducted in March-April 2021. The methods used were observation and in-depth interviews with seven informants: the person in charge of the PKPR program, health workers, peer counselors, and youth participating in PKPR. Results: The results showed that the PKPR program was aligned with the 2014 standard guidelines. This research was done inside and outside the health center by collaborating with PKPR's person in charge and the health team based on the Decree of PKPR implementation. PKPR program is held in three schools in the working area of the West Lingkar Health Center and provides services such as health checks, counseling, and education about youth health. The peer counselor training subprogram has fulfilled the standard 10% of the target schools. PKPR is fully funded by the Special Operational Assistance or Bantuan Operasional Khusus (BOK) fund. Recording and reporting were done every two to three months to the public health office. Monitoring was reported during the activities, while the evaluation report is annual. This research discovered the availability of counseling rooms and related references about communication, information, and education books on PKPR. This research had collaborated with cross-sectors such as schools and the National Antinarcotics Agency. Conclusion:Â  Implementation is under PKPR guidelines, but overall it was still not optimal. There was no regular socialization of PKPR, especially for youth who did not attend school.